Safety evaluation of oral toxicity of potential anticancer agents: An acute and sub-chronic toxicity studies of combinations of Carica Papaya Linn, Vernonia Amygdalina Delile and dihydroartemisinin. (African Journal of Biomedical Research, 2021)
Background: The increase in cancer prevalence rate worldwide is a public health concern. Studies have recognized the use of  phytomedicines in cancer treatment but their safety data is deficient. Vernonia amygdalina Delile (VA), Carica papaya Linn (CP) , and dihydroartemisinin (DHA) have been previously reported to have anti-cancer activities but their safety profiles when combined have not been validated.Materials and methods: Pilot toxicity study was carried out to determine  doses for acute and sub-chronic toxicity studies of the two combined plant extracts  and   compound  in albino mice (n=10) and Wistar rats (n=18). The experiment was done based OECD guidelines. Animals  were dosed with 500, 1,000 and 2,000 mg/kg of drug combinations and observed for 24 hours and 90 days. Hematological, biochemical parameters and histopathological changes  of liver and kidney were evaluated.Results: Drugs administration up to 5, 000 mg/kg  did not cause mortality ( LD50  > 5, 000mg/kg) and concentrations of 2,000 mg/kg  (acute study) did not show observed  toxicity. There was no significant difference in body weight between the treated and control animals in 90 days study although there were  observed significant differences in some hematology and biochemistry parameters. Histopathological examination of the liver and kidney did not reveal organ alterations.Conclusions: Although there were significant changes in hematological and biochemistry parameters, based on all results analysis and OECD classification of formulas as category 5, studied combinations  might not cause known toxicity.